PENGARUH CITRA DESTINASI TERHADAP WORD OF MOUTH (WOM) YANG DIMEDIASI OLEH KEPUASAN PENGUNJUNG DAN DIMODERASI OLEH JENIS KELAMIN - Ika Susilowati (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2019)
The purpose of this research was to analyze the effect of destination images on word of mouth (WOM) mediated by visitor satisfaction and moderated by gender in tourism places in Purwokerto. Data collection was carried out by questionnaires, using a Likert Level Scale 7. This study sampled 125 respondents who had traveled to Purwokerto. The data analysis technique used in this study is the Structural Equation Model (SEM) analysis. The results of this study indicate that destination image has a positive effect on word of mouth (WOM). Destination image has a positive effect on visitor satisfaction. Visitor satisfaction has a positive effect on word of mouth (WOM). The effect of visitor satisfaction mediates the relationship between destination image and word of mouth (WOM). Gender influences the relationship between destination image and word of mouth (WOM). Keywords: Destination Images, word of mouth (WOM), Visitor Satisfaction, Gender